Naherholungsverhalten von Senioren ind der Großstadt.: Eine sozialgeographische Untersuchung am Beispiel Köln - Weiss, Günther (ERDKUNDE, 1991)
This investigation deals with the open-air recreational behaviour of senior citizens and consequently contributes to the geography of elderly people, which grows more and more important in face of the increasing share of elderly people in modern societies. Counting visitors in various typical open-air recreation areas of Cologne, a remarkable concentration of senior citizens, namely women in groups, could be seen in one of them. To explain this phenomenon, elderly visitors were interviewed during their travel in this area and a few of them were interviewed more intensively in some clubs for senior citizens. These elderly women are mostly widows, who do not possess a driving licence and prefer woodland areas with cafes, which can be easily re ached by urban public transportation services, especially by trams. Their recreational activities - walking and visiting cafes - are dependent on norms for typical female leisure behaviour in pre-war-society. Whether an open-air recreation area is visited by an elderly woman depends on the existence of a partner for such excursions. The lack of a driving licence - equally typical for women born before the Second World War -, health status and the perception of dangers determine the action space.